2013
DOI: 10.3109/17518423.2013.807884
|View full text |Cite
|
Sign up to set email alerts
|

Autism severity as a predictor of inattention and impulsivity in toddlers

Abstract: ASD symptom severity predicts rates of ADHD symptoms in atypically developing toddlers. The implications of these findings are discussed in the context of other research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Work in atypically developing toddlers aged 18–37 months suggested ASD symptom severity was positively and significantly associated with inattention/impulsivity (Tureck et al 2013). Follow-up studies of educational attainment for children with combined ASD and ADHD symptoms are needed to determine the impact of such symptoms on academic achievement and other crucial outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Work in atypically developing toddlers aged 18–37 months suggested ASD symptom severity was positively and significantly associated with inattention/impulsivity (Tureck et al 2013). Follow-up studies of educational attainment for children with combined ASD and ADHD symptoms are needed to determine the impact of such symptoms on academic achievement and other crucial outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Consistently, a study by Gordon et al 26 demonstrated that genetic variation in the dopamine transporter (DAT) impacts cross-network connectivity that correlates with measures of impulsivity and inattention, two features of both ASD and ADHD. 27 These data underscore the significance of determining the molecular mechanisms underlying impairments within the dopaminergic system associated with ASD and related disorders with the intent to further define the etiology of this devastating disease.…”
Section: Introductionmentioning
confidence: 95%
“…Level of infant autism features was positively correlated with internalizing symptoms, but unrelated to externalizing symptoms. The latter nonsignificant association might be due to the young age and limited behavioral repertoire of our sample, as a positive correlation between autism and externalizing symptoms been reported among autistic preschoolers [Tureck, Matson, Cervantes, & Turygin, 2015]. Furthermore, level of autism features was negatively correlated with temperamental surgency but unrelated to orienting/ regulation and negative affectivity; consequently, the nonsignificant interaction of AOSI Total and negative affectivity in the mediation models was not all that surprising.…”
Section: Discussionmentioning
confidence: 55%